Sustainable approach on cement mortar incorporating silica fume, LLDPE and sisal fiber. (2022) - Subharaj, C.; Logesh, M.; Abdul Munaf, A.; Srinivas, J.; Joe Patrick Gnanaraj, S.
Abstract: This paper examines the potential of a novel ecological bio product for structural sustainability as well as its role in increasing the brightness and hardness of cement mortar. The overarching goal of incorporating crucial environmental, social, and economic issues into the decision-making process is the focus of a sustainability approach. Sustainability problems aren't new, and they've traditionally been discussed informally or indirectly. In recent years, significant attempts have been made to quantify property effects and to integrate a wide range of property practices in a systematic and orderly manner. These sustainable best practices do not achieve property, but they are improvements on current common practice and show progress toward property, as stated below. The cement mortar used in this study is made out of a mix of cement with other materials. The cement mortar used in this experiment is a combination of cement and sand. The use of a large amount of cement increases natural resource and electricity consumption however, this issue can be handled by substituting another material for cement. The investigations revealed that while LLDPE-based mortar is appropriate for plastering, the amount of material wasted due to material bouncing from plastered surfaces increases as the LLDPE percentage increases. As a result, it is proposed that LLDPE be used for plastering and flooring. The use of sisal fiber improves mechanical characteristics and reduces void content. A compressive strength and temperature test values were performed on all cement mortar cube combinations.